Structure and biological functions of milk caseins - Stanislava Yu. Petrova; Svetlana V. Khlgatian; Olga Yu. Emelyanova; Larisa A. Pishulina; Valentina M. Berzhets (Russian Open Medical Journal)
Caseins, which are contained in milk, play a significant role in the development of clinical symptoms of allergic reactions in adults and children. To date, the properties of caseins have been studied, their primary structure has been identified. However, despite available scientific reviews and original articles, an issue of the structural organization of milk casein micelles and their biological functions is still very controversial. In this regard, the proposed review is relevant, since it most fully reflects current information about various types of caseins, their physicochemical and immunobiological properties, and analyzes in detail the existing theories on the structural organization of casein micelles. Of particular interest in our review are the data on the comparative analysis of the structure and properties of caseins in both human breast milk and cow’s milk, as well as the section dealing with the allergenic activity of cow’s milk caseins and their cross-reactivity with milk proteins of other mammalian species. The objective of this review is to summarize current data on the structure and properties of casein proteins, and to determine their role in the formation of sensitization to dairy products.